MECHANICAL ENGINEERING AND METALWORKING IN THE DEVELOPMENT OF THE NATIONAL ECONOMY - Gavkhar Zokirova (Research Parks Publishers, 2021)
The national economy consists of a complex of many industries, each of which contributes differently to the development of the country. However, there are industries that determine the technical progress of the whole country and make a significant contribution to the innovative development of the economy. One such sector is the machinery sector, which is the main driving force of economic growth